2011
DOI: 10.1097/cco.0b013e32834479c0
|View full text |Cite
|
Sign up to set email alerts
|

Update on targeted therapies for clear cell renal cell carcinoma

Abstract: Summary VEGF and mTOR-targeted therapies continue to play a critical role in the management of advanced and metastatic RCC. Ongoing research to identify novel agents continues to build upon the work done during the elucidation of the VHL/clear cell RCC pathway. It is hoped that ongoing and planned studies will enable development of therapeutic regimens that will incorporate agents with improved toxicity and better efficacy as well as defining a role for a multidisciplinary approach to the management of advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 48 publications
3
40
0
1
Order By: Relevance
“…In conclusion, metastatic RCC is generally associated with a poor prognosis (2); few patients experience long-term survival following surgery, and the clinical application of targeted drugs, including interferon immunotherapy, may improve patient survival (21). In the current case, the patient underwent simultaneous right nephrectomy, left adrenalectomy and segmental pancreatectomy, followed by receipt of interferon immunotherapy for 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, metastatic RCC is generally associated with a poor prognosis (2); few patients experience long-term survival following surgery, and the clinical application of targeted drugs, including interferon immunotherapy, may improve patient survival (21). In the current case, the patient underwent simultaneous right nephrectomy, left adrenalectomy and segmental pancreatectomy, followed by receipt of interferon immunotherapy for 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, the combination therapy of gemcitabine and S-1 has shown a better RR [9]. Sorafenib, a multitargeted kinase inhibitor, has been approved by the United States Food and Drug Administration (FDA) for the treatment of unresectable hepatocellular carcinoma [30] and advanced renal cell carcinoma [31]. However, another study showed that sorafenib did not produce a satisfactory RR for CCA treatment [32].…”
Section: Western Blotting Analysis For Signal Pathwaysmentioning
confidence: 98%
“…Despite considerable advances in our ability to manage advanced RCC, this disease continues to have a significant public health impact(1, 2). In the United States, RCC is currently the sixth and eighth most common malignancy among men and women, respectively, with 63,920 new cases and 13,860 deaths estimated in 2014(3).…”
Section: Introductionmentioning
confidence: 99%